Therapeutic peptides targeting the Ras superfamily. Issue 6 (13th April 2020) - Hurd, Catherine A.; Mott, Helen R.; Owen, Darerca
Abstract: The Ras superfamily of small GTPases are master regulators of numerous essential processes within the cell, so that when they malfunction, cancer and many other diseases can result. For example, activating Ras mutations are present in approximately 20% of human cancers. As such, they are key therapeutic targets, yet more than three decades of intensive research efforts have failed to produce effective Ras inhibitors in the clinic. This is, in part, due to their relatively smooth surfaces which are difficult to target through traditional drug discovery methods using small molecules. Peptides offer a solution to this issue as they occupy larger surface areas on their targets and therefore offer exquisite selectivity and affinity. However, their use in the past has been limited to extracellular targets due to delivery issues. Recent advances in peptide macrocyclisation, modifications and delivery methods have ignited increased interest in the use of these highly effective biologics for intracellular targets. This review will cover progress made in the development of peptides targeting small GTPases to treat a wide range of diseases. Abstract :